The effects of single and multiple BOPPPS-integrated model sessions on public health students' competences: a two-stage study combining quasi-experimental and cross-sectional analyses - Qiqi Liu; Jixuan Ma; Chuansha Wu; Yang Du; Ting Chen; Xiaojie Sun; Qin Zhao; Yunhao Liu; Yuqin Shi; Yingying Gu; Min Zhou; Ling Zhang; et al. (BMC Medical Education)
Abstract Background Effective instructional approaches for fostering students' competences in public health education remain to be explored. This study aimed to integrate the bridge-in, objective, pre-assessment, participatory learning, post-assessment, and summary (BOPPPS) framework with problem-based learning (PBL), team-based learning (TBL), and case-based learning (CBL) to develop a novel instructional model, termed the BOPPPS-integrated model (BIM), and to assess the influences of single and multiple BIM interventions on the competences of undergraduate public health students. Methods A two-stage study was conducted by a quasi-experimental pilot study and a cross-sectional survey. First, the quasi-experiment compared a traditional lecture-based learning (LBL) group (n = 50) with a BIM group (n = 48) to evaluate the effect of a single BIM intervention. Second, a cross-sectional study was conducted to analyze the impacts of multiple BIM sessions across three groups: control (n = 96), basic intervention (1–2 times BIM, n = 66), and intensive intervention (≥ 3 times BIM, n = 62). All participants completed a self-administered questionnaire designed to evaluate seven competence dimensions: information literacy, summarization, expressive communication, critical thinking, self-directed learning, teamwork, and objective evaluation, which are essential for public health students to address complex public health challenges. Results Students who received single and multiple BIM instructional sessions scored significantly higher in information literacy, expressive communication, and teamwork than those who received LBL method (P < 0.05). Multiple BIM interventions further improved scores in summarization, self-directed learning, and objective evaluation (P < 0.05). The scores of six dimensions like information literacy, summarization, expressive communication, self-directed learning, teamwork, and objective evaluation showed an upward trend as the number of interventions increased (P for trend < 0.05). Conclusions A single BIM intervention effectively improved students’ competences in information literacy, teamwork, and expressive communication. Additionally, multiple BIM interventions not only consolidated these competences but also fostered summarization, self-directed learning, and objective evaluation, thereby highlighting the importance of BIM in developing students’ competences in public health education.